Impact of anticoagulant treatment strategy during initiation of antiarrhythmic drugs on clinical outcomes in atrial fibrillation patients with low CHA2DS2-VASc scores - Ahmed B. Elawad; Taylor J. Billion; Alex Hall; Michael H. Kim (Next Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Management considerations for establishing a coastal acidification monitoring system from U.S. Coastal Acidification Networks - Elizabeth K. Wright-Fairbanks; Natalie Lord; Darcy Dugan; Kaitlin Goldsmith; Emily R. Hall; Alex Harper; Janet J. Reimer; Samantha Siedlecki; Elizabeth J. Turner; Jennifer Vreeland-Dawson; Kirstin Wakefield; Kimberly K. Yates (Environmental Monitoring and Assessment, 2025)
Ocean acidification (OA), caused by the uptake of anthropogenic carbon dioxide, is a concern for ocean resource users in coastal regions where the phenomenon is compounded by variable processes. Sustained OA monitoring systems are critical for characterization of baseline ocean conditions and identification of changes and impacts to coastal ecosystems and communities. Establishing an OA monitoring network is best accomplished through iterative planning, sustained funding, and comprehensive understanding of the coastal system. This paper offers decision-making considerations for entities interested in establishing a local to regional scale OA observing system. Such considerations include which carbon system parameters can be measured in each system, which sensors and platforms will provide applicable information for interested partners, and best practices for observing data management. Because every region faces unique circumstances, we present context-specific examples of effective decision-making processes from established U.S. OA observing networks. These regional case studies offer information on specific scientific questions, observing techniques, and methodology employed to establish and manage OA observations in the coastal zone.

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Capturing exposed bedrock in the upland regions of Great Britain: A geomorphometric focused random forest approach - Chris Williams; Katie Whitbread; Alex Hall; Sam Roberson; Andrew Finlayson; Romesh N. Palamakumbura; Andrew Hulbert; Matthew Paice (Computers & Geosciences, 2025)

Correction to: Human-induced changes in wind, temperature and relative humidity during Santa Ana events - Mimi Rose Abel; Alex Hall; Jinwon Kim (Climatic Change, 2025)

Correction to: Dynamical controls on the diurnal cycle of temperature in complex topography - Mimi Rose Abel; Alex Hall; Robert G. Fovell (Climate Dynamics, 2025)

Correction to: El Nin˜o-Southern Oscillation impacts on winter winds over Southern California - Neil Berg; Alex Hall; Scott B. Capps; Mimi Rose Abel (Climate Dynamics, 2025)

Correction: Local and synoptic mechanisms causing Southern California’s Santa Ana winds - Mimi Rose Abel; Alex Hall (Climate Dynamics, 2025)

Preconditioning blasting for rockburst control in a deep shaft sink - Alex Hall; Brad Simser; Ming Cai; Jared Lindsay (International Journal of Rock Mechanics and Mining Sciences, 2024)

Diagnosis and treatment of an oral, migrating foreign body penetrating the spinal cord in a rabbit (Oryctolagus cuniculus) - Margaret Cook; Amanda L. Day; Catriona MacPhail; Becky Pacheco; Anna Price; Camilla Cooper; Kelly Hall; Alex Ohlendorf; Miranda J. Sadar (Journal of Exotic Pet Medicine, 2024)

Wastewater-based monitoring of the nitazene analogues: First detection of protonitazene in wastewater - Richard Bade; Dhayaalini Nadarajan; Erin M. Driver; Rolf U. Halden; Cobus Gerber; Alex Krotulski; Wayne Hall; Jochen F. Mueller (Science of The Total Environment, 2024)

Community composition of bacteria isolated from Swiss banknotes varies depending on collection environment - Anna M. Bischofberger; Alex R. Hall (Molecular Ecology, 2023)
Humans interact constantly with surfaces and associated microbial communities in the environment. The factors shaping the composition of these communities are poorly understood: some proposed explanations emphasize the influence of local habitat conditions (niche‐based explanations), while others point to geographic structure and the distance among sampled locations (dispersal‐based explanations). However, the relative roles of these different drivers for microbial community assembly on human‐associated surfaces are not clear. Here, we used a combination of sampling, sequencing (16S rRNA) and culturing to show that the composition of banknote‐associated bacterial communities varies depending on the local collection environment. Using banknotes collected from various locations and types of shops across Switzerland, we found taxonomic diversity dominated by families such as Pseudomonadaceae and Staphylococcaceae , but with banknote samples from particular types of shops (especially butcher shops) having distinct community structure. By contrast, we found no evidence of geographic structure: similarity of community composition did not decrease with increasing distance among sampled locations. These results show that microbial communities associated with banknotes, one of the most commonly encountered and exchanged human‐associated surfaces, can reflect the local environmental conditions (in this case, the type of shop), and the signal for this type of variation was stronger than that for geographic structure among the locations sampled here.

Towards effective reforestation: growth and commercial value of four commonly planted tropical timber species on infertile soils in Panama - Katherine Sinacore; Edwin H. García; Theodore Howard; Michiel van Breugel; Omar R. Lopez; Alex J. Finkral; Jefferson S. Hall (New Forests, 2023)
Finding suitable tree species that not only grow well on nutrient poor soils but are also safe financial investments is one of the major obstacles to successful reforestation efforts in the tropics. Our study compared the financial viability and growth of valuable timber species in monocultures and mixtures on infertile soils. Our work shows the extraordinary growth in volume and value of Dalbergia retusa and Terminalia amazonia while underscoring the poor financial viability of Tectona grandis and Pachira quinata , all commonly planted timber species in Panama and much of Central and South America. Using Bayesian statistics, our predictions show that T. amazonia monocultures could reach nearly 200 m 3 ha −1 of merchantable volume after 30 years compared to the ~ 40 m 3 ha −1 that T. grandis could accumulate in the same time frame. While D. retusa monocultures did not have the highest predicted merchantable volumes of all the species, it did have the highest predicted net present value (NPV), with a predicted mean NPV of > US$97,000 ha −1 , quadrupling the species with the next highest monoculture’s NPV, T. amazonia monocultures (~ US$20,000 ha −1 ). Our work emphasizes that reforestation can be financially viable on low nutrient soils, even in the absence of fertilization or other silvicultural manipulations, if species selection and site are carefully considered and matched.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Shallowness of tropical low clouds as a predictor of climate models’ response to warming - Florent Brient; Tapio Schneider; Zhihong Tan; Sandrine Bony; Xin Qu; Alex Hall (Climate Dynamics, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Associations between sensitivity to antibiotics, disinfectants and heavy metals in natural, clinical and laboratory isolates of Escherichia coli - Anna M. Bischofberger; Michael Baumgartner; Katia R. Pfrunder‐Cardozo; Richard C. Allen; Alex R. Hall (Environmental Microbiology, 2020)
Summary Bacteria in nature often encounter non‐antibiotic antibacterials (NAAs), such as disinfectants and heavy metals, and they can evolve resistance via mechanisms that are also involved in antibiotic resistance. Understanding whether susceptibility to different types of antibacterials is non‐randomly associated across natural and clinical bacteria is therefore important for predicting the spread of resistance, yet there is no consensus about the extent of such associations or underlying mechanisms. We tested for associations between susceptibility phenotypes of 93 natural and clinical Escherichia coli isolates to various NAAs and antibiotics. Across all compound combinations, we detected a small number of non‐random associations, including a trio of positive associations among chloramphenicol, triclosan and benzalkonium chloride. We investigated genetic mechanisms that can explain such associations using genomic information, genetic knockouts and experimental evolution. This revealed some mutations that are selected for by experimental exposure to one compound and confer cross‐resistance to other compounds. Surprisingly, these interactions were asymmetric: selection for chloramphenicol resistance conferred cross‐resistance to triclosan and benzalkonium chloride, but selection for triclosan resistance did not confer cross‐resistance to other compounds. These results identify genetic changes involved in variable cross‐resistance across antibiotics and NAAs, potentially contributing to associations in natural and clinical bacteria.

Snow and Climate: Feedbacks, Drivers, and Indices of Change - Chad W. Thackeray; Chris Derksen; Christopher G. Fletcher; Alex Hall (Current Climate Change Reports, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

A Multidisciplinary Approach for Generating Globally Consistent Data on Mesophotic, Deep-Pelagic, and Bathyal Biological Communities - Lucy Woodall; Dominic Andradi-Brown; Andrew Brierley; Malcolm Clark; Douglas Connelly; Rob Hall; Kerry Howell; Veerle Huvenne; Katrin Linse; Rebecca Ross; Paul Snelgrove; Paris Stefanoudis; et al. (Oceanography, 2018)

Low-Cloud Feedbacks from Cloud-Controlling Factors: A Review - Stephen A. Klein; Alex Hall; Joel R. Norris; Robert Pincus (Surveys in Geophysics, 2017)
The response to warming of tropical low-level clouds including both marine stratocumulus and trade cumulus is a major source of uncertainty in projections of future climate. Climate model simulations of the response vary widely, reflecting the difficulty the models have in simulating these clouds. These inadequacies have led to alternative approaches to predict low-cloud feedbacks. Here, we review an observational approach that relies on the assumption that observed relationships between low clouds and the “cloud-controlling factors” of the large-scale environment are invariant across time-scales. With this assumption, and given predictions of how the cloud-controlling factors change with climate warming, one can predict low-cloud feedbacks without using any model simulation of low clouds. We discuss both fundamental and implementation issues with this approach and suggest steps that could reduce uncertainty in the predicted low-cloud feedback. Recent studies using this approach predict that the tropical low-cloud feedback is positive mainly due to the observation that reflection of solar radiation by low clouds decreases as temperature increases, holding all other cloud-controlling factors fixed. The positive feedback from temperature is partially offset by a negative feedback from the tendency for the inversion strength to increase in a warming world, with other cloud-controlling factors playing a smaller role. A consensus estimate from these studies for the contribution of tropical low clouds to the global mean cloud feedback is 0.25 ± 0.18 W m −2 K −1 (90% confidence interval), suggesting it is very unlikely that tropical low clouds reduce total global cloud feedback. Because the prediction of positive tropical low-cloud feedback with this approach is consistent with independent evidence from low-cloud feedback studies using high-resolution cloud models, progress is being made in reducing this key climate uncertainty.

Parasite genetic distance and local adaptation in co‐evolving bacteria–bacteriophage populations - Pauline D. Scanlan; Alex R. Hall; Angus Buckling (Molecular Ecology, 2017)
Antagonistic co‐evolution between hosts and parasites can lead to local adaptation ( LA ) such that parasite fitness is greatest in sympatric hosts (or vice versa). The magnitude of LA typically increases with geographical distance, which is assumed to be because genetic (and hence phenotypic) distance increases with geographical distance. Here, we explicitly test the relationships between parasite genetic and phenotypic distance and LA using isolates of co‐evolved viral parasites (lytic bacteriophage ϕ2) and the host bacterium Pseudomonas fluorescens SBW 25. We find positive relationships between parasite genotype and infectivity phenotype, but the strength of the relationship was greater when infectivity was defined by the identity of hosts that could be infected rather than the actual number of hosts infected (host range), and when measurements were compared within rather than among populations. Crucially, we find a monotonic relationship between LA and genetic distance across phage isolates from different populations, although in contrast to many geographical studies, parasite LA decreased with genetic distance. These results can be explained by the fact that bacteria can rapidly adapt to phage infectivity mutations, but that evolved resistance has a degree of specificity to the local phage population. Our results show that antagonistic co‐evolution alone can result in predictable links between genetic distance and host–parasite local adaptation.

Identifying gene–gene interactions that are highly associated with four quantitative lipid traits across multiple cohorts - Rishika De; Shefali S. Verma; Emily Holzinger; Molly Hall; Amber Burt; David S. Carrell; David R. Crosslin; Gail P. Jarvik; Helena Kuivaniemi; Iftikhar J. Kullo; Leslie A. Lange; Matthew B. Lanktree; et al. (Human Genetics, 2017)

Shallowness of tropical low clouds as a predictor of climate models’ response to warming - Florent Brient; Tapio Schneider; Zhihong Tan; Sandrine Bony; Xin Qu; Alex Hall (Climate Dynamics, 2016)

A physically-based hybrid framework to estimate daily-mean surface fluxes over complex terrain - Hsin-Yuan Huang; Alex Hall (Climate Dynamics, 2016)

Orographic shaping of US West Coast wind profiles during the upwelling season - Lionel Renault; Alex Hall; James C. McWilliams (Climate Dynamics, 2016)

Emergent Constraints for Cloud Feedbacks - Stephen A. Klein; Alex Hall (Current Climate Change Reports, 2015)

The strength of the tropical inversion and its response to climate change in 18 CMIP5 models - Xin Qu; Alex Hall; Stephen A. Klein; Peter M. Caldwell (Climate Dynamics, 2015)

Downscaling near-surface wind over complex terrain using a physically-based statistical modeling approach - Hsin-Yuan Huang; Scott B. Capps; Shao-Ching Huang; Alex Hall (Climate Dynamics, 2015)

Higher resources decrease fluctuating selection during host–parasite coevolution - Laura Lopez Pascua; Alex R. Hall; Alex Best; Andrew D. Morgan; Mike Boots; Angus Buckling (Ecology Letters, 2014)
We still know very little about how the environment influences coevolutionary dynamics. Here, we investigated both theoretically and empirically how nutrient availability affects the relative extent of escalation of resistance and infectivity (arms race dynamic; ARD ) and fluctuating selection (fluctuating selection dynamic; FSD ) in experimentally coevolving populations of bacteria and viruses. By comparing interactions between clones of bacteria and viruses both within‐ and between‐time points, we show that increasing nutrient availability resulted in coevolution shifting from FSD , with fluctuations in average infectivity and resistance ranges over time, to ARD . Our model shows that range fluctuations with lower nutrient availability can be explained both by elevated costs of resistance (a direct effect of nutrient availability), and reduced benefits of resistance when population sizes of hosts and parasites are lower (an indirect effect). Nutrient availability can therefore predictably and generally affect qualitative coevolutionary dynamics by both direct and indirect (mediated through ecological feedbacks) effects on costs of resistance.

On the spread of changes in marine low cloud cover in climate model simulations of the 21st century - Xin Qu; Alex Hall; Stephen A. Klein; Peter M. Caldwell (Climate Dynamics, 2014)

The ventral pallidum and orbitofrontal cortex support food pleasantness inferences - W. Kyle Simmons; Kristina M. Rapuano; John E. Ingeholm; Jason Avery; Seth Kallman; Kevin D. Hall; Alex Martin (Brain Structure and Function, 2014)

On the persistent spread in snow-albedo feedback - Xin Qu; Alex Hall (Climate Dynamics, 2014)

A regional modeling study of the diurnal cycle in the lower troposphere in the south-eastern tropical Pacific - Thomas Toniazzo; Fengpeng Sun; Carlos R. Mechoso; Alex Hall (Climate Dynamics, 2013)

El Niño-Southern Oscillation impacts on winter winds over Southern California - Neil Berg; Alex Hall; Scott B. Capps; Mimi Rose Abel (Climate Dynamics, 2013)

Real‐time PCR assays for the identification of harbor and gray seal species and sex: A molecular tool for ecology and management - Iveta Matejusová; Fiona Bland; Ailsa J. Hall; Robert N. Harris; Michael Snow; Alex Douglas; Stuart J. Middlemas (Marine Mammal Science, 2013)

Global habitat suitability of cold‐water octocorals - Chris Yesson; Michelle L. Taylor; Derek P. Tittensor; Andrew J. Davies; John Guinotte; Amy Baco; Julie Black; Jason M. Hall‐Spencer; Alex D. Rogers (Journal of Biogeography, 2012)
Aim Three‐quarters of Octocorallia species are found in deep waters. These cold‐water octocoral colonies can form a major constituent of structurally complex habitats. The global distribution and the habitat requirements of deep‐sea octocorals are poorly understood given the expense and difficulties of sampling at depth. Habitat suitability models are useful tools to extrapolate distributions and provide an understanding of ecological requirements. Here, we present global habitat suitability models and distribution maps for seven suborders of Octocorallia: Alcyoniina, Calcaxonia, Holaxonia, Scleraxonia, Sessiliflorae, Stolonifera and Subselliflorae. Location Global. Methods We use maximum entropy modelling to predict octocoral distribution using a database of 12,508 geolocated octocoral specimens and 32 environmental grids resampled to 30 arc‐second (approximately 1 km 2 ) resolution. Additionally, a meta‐analysis determined habitat preferences and niche overlap between the different suborders of octocorals. Results Suborder Sessiliflorae had the widest potential habitat range, but all records for all suborders implied a habitat preference for continental shelves and margins, particularly the North and West Atlantic and Western Pacific Rim. Temperature, salinity, broad scale slope, productivity, oxygen and calcite saturation state were identified as important factors for determining habitat suitability. Less than 3% of octocoral records were found in waters undersaturated for calcite, but this result is affected by a shallow‐water sampling bias. Main conclusions The logistical difficulties, expense and vast areas associated with deep‐sea sampling leads to a gap in the knowledge of faunal distributions that is difficult to fill without predictive modelling. Global distribution estimates are presented, highlighting many suitable areas which have yet to be studied. We suggest that approximately 17% of oceans are suitable for at least one suborder but 3.5% may be suitable for all seven. This is the first global habitat suitability modelling study on the distribution of octocorals and forms a useful resource for researchers, managers and conservationists.

Causes of recent changes in western North American snowpack - Sarah Kapnick; Alex Hall (Climate Dynamics, 2012)

Why does the Antarctic Peninsula Warm in climate simulations? - Xin Qu; Alex Hall; Julien Boé (Climate Dynamics, 2012)

Human-induced changes in wind, temperature and relative humidity during Santa Ana events - Mimi Rose Abel; Alex Hall; Jinwon Kim (Climatic Change, 2011)

What shapes mesoscale wind anomalies in coastal upwelling zones? - Julien Boé; Alex Hall; François Colas; James C. McWilliams; Xin Qu; Jaison Kurian; Sarah B. Kapnick (Climate Dynamics, 2011)

Atmospheric inversion strength over polar oceans in winter regulated by sea ice - Tamlin M. Pavelsky; Julien Boé; Alex Hall; Eric J. Fetzer (Climate Dynamics, 2011)

Genetic basis of infectivity evolution in a bacteriophage - PAULINE D. SCANLAN; ALEX R. HALL; LAURA D. C. LOPEZ‐PASCUA; ANGUS BUCKLING (Molecular Ecology, 2011)
Antagonistic coevolution between hosts and parasites is probably ubiquitous. However, very little is known of the genetic changes associated with parasite infectivity evolution during adaptation to a coevolving host. We followed the phenotypic and genetic changes in a lytic virus population (bacteriophage; phage Φ2) that coevolved with its bacterial host, Pseudomonas fluorescens SBW25. First, we show the rapid evolution of numerous unique phage infectivity phenotypes, and that both phage host range and bacterial resistance to individual phage increased over coevolutionary time. Second, each of the distinct phage phenotypes in our study had a unique genotype, and molecular evolution did not act uniformly across the phage genome during coevolution. In particular, we detected numerous substitutions on the tail fibre gene, which is involved in the first step of the host–parasite interaction: host adsorption. None of the observed mutations could be directly linked with infection against a particular host, suggesting that the phenotypic effects of infectivity mutations are probably epistatic. However, phage genotypes with the broadest host ranges had the largest number of nonsynonymous amino acid changes on genes implicated in infectivity evolution. An understanding of the molecular genetics of phage infectivity has helped to explain the complex phenotypic coevolutionary dynamics in this system.

Seamounts as refugia from ocean acidification for cold‐water stony corals - Derek P. Tittensor; Amy R. Baco; Jason M. Hall‐Spencer; James C. Orr; Alex D. Rogers (Marine Ecology, 2010)
Cold‐water stony corals create habitat for a diverse range of deep‐water species but are thought to be threatened by ocean acidification due to oceanic uptake of anthropogenic CO 2 . Knowledge of the severity of this threat is hampered by our limited understanding of the distribution and habitat requirements of these corals. Here we estimate the global acidification threat to these organisms using a global database of cold‐water stony coral records and a species distribution modelling approach. We parameterised the models using present‐day environmental data, and then replaced these data with future projections of ocean chemistry from the year 2099. We found suitable coral habitat to be very heterogeneously distributed, being concentrated in the northern North Atlantic and around New Zealand. Projected changes in ocean chemistry induced a pronounced reduction in habitat suitability in the North Atlantic, and a low‐to‐moderate impact elsewhere under both the IPCC IS92a and S650 scenarios. Seamount summits are impacted by these changes, but consistently provide more suitable habitat than the surrounding seafloor, with around 98% of seamount summits having higher suitability in both future scenarios; this is because they lie in shallower waters with a higher aragonite saturation state. These results suggest that anthropogenic‐induced changes in ocean chemistry are likely to severely impact cold‐water stony coral habitat in the deep‐sea of the North Atlantic, and that impacts will be less severe elsewhere. We predict that coral communities on the summits and upper slopes of seamounts will be less susceptible to ocean acidification during this century than those on the surrounding seafloor, and thus that seamounts may serve as temporary refugia.

Local and synoptic mechanisms causing Southern California’s Santa Ana winds - Mimi Rose Abel; Alex Hall (Climate Dynamics, 2010)

Sources of spread in simulations of Arctic sea ice loss over the twenty-first century - Julien Boé; Alex Hall; Xin Qu (Climatic Change, 2010)

Predicting global habitat suitability for stony corals on seamounts - Derek P. Tittensor; Amy R. Baco; Paul E. Brewin; Malcolm R. Clark; Mireille Consalvey; Jason Hall‐Spencer; Ashley A. Rowden; Thomas Schlacher; Karen I. Stocks; Alex D. Rogers (Journal of Biogeography, 2009)
Aim Globally, species distribution patterns in the deep sea are poorly resolved, with spatial coverage being sparse for most taxa and true absence data missing. Increasing human impacts on deep‐sea ecosystems mean that reaching a better understanding of such patterns is becoming more urgent. Cold‐water stony corals (Order Scleractinia) form structurally complex habitats (dense thickets or reefs) that can support a diversity of other associated fauna. Despite their widely accepted ecological importance, records of scleractinian corals on seamounts are patchy and simply not available for most of the global ocean. The objective of this paper is to model the global distribution of suitable habitat for stony corals on seamounts. Location Seamounts worldwide. Methods We compiled a database containing all accessible records of scleractinian corals on seamounts. Two modelling approaches developed for presence‐only data were used to predict global habitat suitability for seamount scleractinians: maximum entropy modelling (Maxent) and environmental niche factor analysis (ENFA). We generated habitat‐suitability maps and used a cross‐validation process with a threshold‐independent metric to evaluate the performance of the models. Results Both models performed well in cross‐validation, although the Maxent method consistently outperformed ENFA. Highly suitable habitat for seamount stony corals was predicted to occur at most modelled depths in the North Atlantic, and in a circumglobal strip in the Southern Hemisphere between 20° and 50° S and shallower than around 1500 m. Seamount summits in most other regions appeared much less likely to provide suitable habitat, except for small near‐surface patches. The patterns of habitat suitability largely reflect current biogeographical knowledge. Environmental variables positively associated with high predicted habitat suitability included the aragonite saturation state, and oxygen saturation and concentration. By contrast, low levels of dissolved inorganic carbon, nitrate, phosphate and silicate were associated with high predicted suitability. High correlation among variables made assessing individual drivers difficult. Main conclusions Our models predict environmental conditions likely to play a role in determining large‐scale scleractinian coral distributions on seamounts, and provide a baseline scenario on a global scale. These results present a first‐order hypothesis that can be tested by further sampling. Given the high vulnerability of cold‐water corals to human impacts, such predictions are crucial tools in developing worldwide conservation and management strategies for seamount ecosystems.

Dynamical controls on the diurnal cycle of temperature in complex topography - Mimi Rose Abel; Alex Hall; Robert G. Fovell (Climate Dynamics, 2007)

Comparisons between the biology of two co-occurring species of whiting (Sillaginidae) in a large marine embayment - Peter G. Coulson; S. Alex Hesp; Ian C. Potter; Norman G. Hall (Environmental Biology of Fishes, 2005)

Reproductive Biology and Protandrous Hermaphroditism in Acanthopagrus latus - S. Alex Hesp; Ian C. Potter; Norman G. Hall (Environmental Biology of Fishes, 2004)